Income Analysis of Clove Farmers in Katoi Village Katoi District North Kolaka Regency - Abdullah, Sukmawati; Nadiriyati, Fahria; Syarni, Pertiwi; Jumria, Jumria (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
This study aims to determine clove farmers' total costs and income in Katoi Village, Katoi District, North Kolaka Regency. The study was conducted in July 2019. The population in this study were clove farmers, totaling 142 people, using the simple random sampling method, and 30 clove farmers were obtained as research samples. Data collection techniques in the research used were surveys and interviews. Analysis of the data used in this study using income analysis. Based on income analysis, the results showed that the income of clove farmers in Katoi Village, Katoi District, North Kolaka Regency was IDR. 71,732,455/year with total clove production of 911 kg. Year. While the total cost of clove farmers is IDR. 7,524,545/year.